Rancang Bangun Vertical Clarifier Tank Mini dengan Adjusment Variasi Kedalaman Pipa Inlet untuk Melihat Pengaruh Tingkat Kadar Kotoran pada Minyak Overflow Crude Palm Oil - Ridha, Arrazy Elba; Adib, Adib; Azwanda, Azwanda; Jayadi, Farid; Muzammil, Abdul; Akmal, Abdiel Khaleil; Azhar, Azhar (Universitas Teuku Umar, 2024)
Vertical Clarifier Tank (VCT) has a very crucial role to separate oil, water and sludge by gravity, where oil with a smaller specific gravity of 0.8 grams / cm3 will be in the uppermost layer, while water whose specific gravity is 1 gram / cm3 will be in the middle layer, and sludge with a density of 1.3 grams / cm3 from the Vertical Clarifier Tank (VCT). The experimental design of this study was to determine the appropriate depth of the inlet pipe to obtain low levels of impurities during oil extraction. The results of the study obtained from variations in the depth of 25 cm, 40 cm, 55 cm, and 70 cm inlet pipes used as the inflow of crude oil from Crude Palm Oil with variations in sedimentation time of 100 minutes, 120 minutes, 140 minutes, 160 minutes, 180 minutes, and 200 minutes, obtained the least level of impurities in the Inlet Pipe which has a length of 55 cm with a variable sedimentation time of 200 minutes.